Predictive factors for successful vagus nerve stimulation in patients with refractory epilepsy: real-life insights from a multicenter study - Pires do Prado, Henrique Jannuzzelli; Pinto, Lécio Figueira; Bezerra, Daniela Fontes; de Paola, Luciano; Arruda, Francisco; de Oliveira, Andrea Julião; Romão, Tayla Taynan; Lessa, Vanessa Cristina Colares; Silva, Jonadab dos Santos; D’Andrea-Meira, Isabella (Frontiers in Neuroscience, 2023)
Introduction Vagus nerve stimulation (VNS) therapy is an established treatment for patients with drug-resistant epilepsy that reduces seizure frequency by at least 50% in approximately half of patients; however, the characteristics of the patients with the best response have not yet been identified. Thus, it is important to identify the profile of patients who would have the best response to guide early indications and better patient selection. Methods This retrospective study evaluated vagus nerve stimulation (VNS) as an adjuvant therapy for patients with drug-resistant epilepsy from six epilepsy centers in Brazil. Data from 192 patients aged 2–66 years were analyzed, and all patients received at least 6 months of therapy to be included. Results Included patients were aged 2–66 years (25.6 ± 14.3), 105 (54.7%) males and 87 (45.8%) females. Median follow-up interval was 5 years (range, 2005—2018). Overall, the response rate (≥50% seizure reduction) after VNS implantation was 65.6% (126/192 patients). Most patients had 50–90% seizure reduction (60.9%) and nine patients became seizure-free. There were no serious complications associated with VNS implantation. The rate of a ≥ 50% seizure reduction response was significantly higher in patients with no history of neurosurgery. The presence of focal without generalized seizures and focal discharges on interictal EEG was associated with better response. Overall, etiological predictors of a better VNS response profile were tumors while a worse response to VNS was related to the presence of vascular malformations and Lennox–Gastaut Syndrome. Discussion We observed an association between a better response to VNS therapy no history of neurosurgery, focal interictal epileptiform activity, and focal seizure pattern. Additionally, it is important to highlight that age was not a determinant factor of the response, as children and adults had similar response rates. Thus, VNS therapy should be considered in both adults and children with DRE.